The Association Between Lysosomal Storage Disorder Genes and Parkinson’s Disease: A Large Cohort Study in Chinese Mainland Population - Zhao, Yu-wen; Pan, Hong-xu; Liu, Zhenhua; Wang, Yige; Zeng, Qian; Fang, Zheng-huan; Luo, Teng-fei; Xu, Kun; Wang, Zheng; Zhou, Xun; He, Runcheng; Li, Bin; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Recent years have witnessed an increasing number of studies indicating an essential role of the lysosomal dysfunction in Parkinson’s disease at the genetic, biochemical, and cellular pathway levels. Here we investigated the association between rare variants in lysosomal storage disorders (LSDs) genes and Chinese mainland Parkinson’s disease. Methods: We explored the association between rare variants of 69 LSDs genes and Parkinson’s disease in 3,879 patients and 2,931 controls from Parkinson’s Disease & Movement Disorders Multicenter Database and Collaborative Network in China (PD-MDCNC) using next-generation sequencing, which were analyzed by the optimized sequence kernel association test. Results: We identified the significant burden of rare putative LSDs gene variants in Chinese mainland Parkinson’s disease patients. This association was robust in familial or sporadic early-onset patients after excluding the GBA variants but not in sporadic late-onset patients. The burden analysis of variants sets in genes of LSDs subgroups revealed a suggestive significant association between variants set in genes of Sphingolipidoses deficiency disorders and familial or sporadic early-onset patients. In contrast, variants set in genes of Sphingolipidoses, Mucopolysaccharidoses, and Post-translational modification defects disorders were suggestively associated with sporadic late-onset patients. Next, SMPD1 and other four novel genes (GUSB, CLN6, PPT1, and SCARB2) were suggestively associated with sporadic early-onset or familial patients, whereas GALNS and NAGA were suggestively associated with late-onset patients. Conclusion: Our findings supported the association between LSDs genes and Parkinson’s disease and revealed several novel risk genes in Chinese mainland Parkinson’s disease patients, which confirmed the importance of lysosomal mechanisms in Parkinson’s disease pathogenesis. Moreover, we identified the genetic heterogeneity in early-onset and late-onset Parkinson’s disease patients, which may provide valuable suggestions for the treatment.